2019
DOI: 10.1111/adb.12726
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonsynaptic α1 glycine receptors on ethanol consumption and place preference

Abstract: Alcohol abuse leads to great medical, social, and economic burdens throughout the world. It is believed that the rewarding actions of alcohol are mediated by alterations in the mesolimbic dopaminergic system leading to increased levels of dopamine in the nucleus accumbens (NAc). Little is known about the role that ligand-gated ion channels (LGICs), such as glycine receptors (GlyRs), have in regulating levels of ethanol intake and place preference. In this study, we used knock-in (KI) mice that have ethanol-ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 54 publications
(128 reference statements)
3
38
1
Order By: Relevance
“…This test is a form of Pavlovian conditioning used to measure the rewarding and motivational effects of abused drugs (Cunningham, Gremel, & Groblewski, 2006). It was previously reported that KI mice for the α1 glycine receptor subunit showed increased preference for the ethanol side compared to WT mice, demonstrating the relevance of glycine receptors in the regulation of behaviours related with alcohol seeking (Muñoz et al, 2019). The WT and Glra2 − /Y mice used in the conditioned place preference test did not show preference for either side of the cage during the 15‐min pre‐conditioning session (Figure 7a,c).…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…This test is a form of Pavlovian conditioning used to measure the rewarding and motivational effects of abused drugs (Cunningham, Gremel, & Groblewski, 2006). It was previously reported that KI mice for the α1 glycine receptor subunit showed increased preference for the ethanol side compared to WT mice, demonstrating the relevance of glycine receptors in the regulation of behaviours related with alcohol seeking (Muñoz et al, 2019). The WT and Glra2 − /Y mice used in the conditioned place preference test did not show preference for either side of the cage during the 15‐min pre‐conditioning session (Figure 7a,c).…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies demonstrated that nucleus accumbens expresses glycine receptor α and β subunits (Jonsson et al, 2012; Muñoz et al, 2019). Analysis of glycine receptor subunit relative expression in the nucleus accumbens using real‐time PCR revealed high levels of α2 and β subunits in WT mice, while in the Glra2 − /Y mice, the expression of α2 was completely abolished, as expected (Figure 1a).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations